Pensare la differenza dalla storia allo spazio. Adorno incontra Deleuze - Cerchi, Giampaolo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
This paper intends to make a comparison between Theodor Adorno’s and Gilles Deleuze’s approaches to the problem of difference. This notion is developed in different ways by these two thinkers: in Adorno’s view, the difference is an irreconcilable power of opposition, whereas, according to Deleuze, does not derive from the concept of identity. Despite their different perspectives, this paper aims to emphasize some common points between the German and French thinkers. Such common points can be tracked down by comparing Adorno’s concept of constellation and Deleuze’s notion of rhizome. Both these concepts propose a logic of relation that, on the one hand, rejects the hierarchical primacy of identity and, on the other hand, attempts to overcome the classical philosophy of history. It is in this context that Adorno and Deleuze provide an original interpretation of space as the most fruitful perspective to conceive of difference.